Role of the P-Type ATPases, ATP7A and ATP7B in brain copper homeostasis - Telianidis, Jonathon; Hung, Ya Hui; Materia, Stephanie; La Fontaine, Sharon (Frontiers in Aging Neuroscience, 2013)
Over the past two decades there have been significant advances in our understanding of copper homeostasis and the pathological consequences of copper dysregulation. Cumulative evidence is revealing a complex regulatory network of proteins and pathways that maintain copper homeostasis. The recognition of copper dysregulation as a key pathological feature in prominent neurodegenerative disorders such as Alzheimer’s, Parkinson’s and prion diseases has led to increased research focus on the mechanisms controlling copper homeostasis in the brain. The copper-transporting P-Type ATPases (copper-ATPases), ATP7A and ATP7B, are critical components of the copper regulatory network. Our understanding of the biochemistry and cell biology of these complex proteins has grown significantly since their discovery in 1993. They are large polytopic transmembrane proteins with six copper-binding motifs within the cytoplasmic N-terminal domain, eight transmembrane domains and highly conserved catalytic domains. These proteins catalyze ATP-dependent copper transport across cell membranes for the metallation of many essential cuproenzymes, as well as for the removal of excess cellular copper to prevent copper toxicity. A key functional aspect of these copper transporters is their copper-responsive trafficking between the trans-Golgi network and the cell periphery. ATP7A- and ATP7B-deficiency, due to genetic mutation, underlie the inherited copper transport disorders, Menkes and Wilson diseases, respectively. Their importance in maintaining brain copper homeostasis is underscored by the severe neuropathological deficits in these disorders. Herein we will review and update our current knowledge of these copper transporters in the brain and the central nervous system, their distribution and regulation, their role in normal brain copper homeostasis and how their absence or dysfunction contributes to disturbances in copper homeostasis and neurodegeneration.